Pemilihan Pemasok Bahan Makanan pada Kafetaria Universitas XYZ: Penerapan Metode MARCOS untuk Keputusan Multikriteria - George Morris William Tangka; Raissa Camila Maringka; Erienika Meiling Lompoliu (Universitas Veteran Bangun Nusantara, 2025)
The cafeteria of XYZ University serves as an essential service hub for students, especially dormitory residents, so the selection of food suppliers must systematically consider quality, food safety, delivery reliability, service, and cost. This study aims to formulate a transparent and replicable multi-criteria decision-making model for selecting food suppliers for a university cafeteria. Five criteria are used in the evaluation, namely quality and freshness (C1), delivery reliability (C2), compliance with food safety standards (C3), service responsiveness (C4), and price (C5), applied to four supplier alternatives (Alpha, Beta, Gamma, Delta). The criteria weights are determined based on expert judgments and normalized so that their sum equals one. The MARCOS method is implemented through six main stages: construction of the decision matrix, determination of ideal and anti-ideal alternatives, normalization according to criteria type, weighting, calculation of aggregate scores, and computation of utility degrees relative to the ideal and anti-ideal conditions. The results show the final ranking Alpha > Gamma > Beta > Delta, with Alpha having the highest utility value and Delta the lowest. Sensitivity analysis with moderate variations in the weights indicates that the ranking remains stable, suggesting that the decision is robust against reasonable changes in policy preferences. In practical terms, the proposed model provides a numerical framework that is easy to audit and communicate to non-technical stakeholders, and can serve as a basis for procurement policy formulation and periodic evaluation of supplier performance in university cafeteria settings.